Towards an integrative theory of psychogenic non-epileptic seizures (PNES). (July 2016) - Brown, Richard J.; Reuber, Markus
Abstract: Psychogenic Nonepileptic Seizures (PNES) superficially resemble epileptic seizures but are thought to have a psychological rather than epileptic basis. Patients with PNES vary widely in terms of background, personality profiles, comorbidities, response to treatment and outcomes. Previous accounts interpreting these seizures as the activation of dissociated material, a physical manifestation of emotional distress, hard-wired reflex responses, or learned behaviours cannot explain key features of the phenomenon. Drawing on a brief review of the literature on etiology, correlates and phenomenology of PNES, this paper integrates existing approaches and data within a novel explanatory framework that applies to all PNES patients with subjectively involuntary seizures. Following the Integrative Cognitive Model of medically unexplained symptoms, we suggest that the central feature of all PNES is the automatic activation of a mental representation of seizures (the "seizure scaffold") in the context of a high level inhibitory processing dysfunction. This often arises in response to elevated autonomic arousal, and may disrupt the individual's awareness of distressing material, but can become divorced from abnormal autonomic and emotional activity. This model accounts both for existing findings and the heterogeneity of patients with PNES, whilst leading to a number of novel hypotheses against which it can be evaluated. Highlights: Current models of PNES can account for some but not all of the available data. Automatic activation of seizure representations in memory may be a unifying process. Suppression of arousal and distress are typical maintaining factors for PNES. Inhibitory dysfunction, often arising from chronic stress, is a key vulnerability. Trauma exposure is common but neither necessary nor sufficient for PNES to occur.